HyPhy 2.5—A Customizable Platform for Evolutionary Hypothesis Testing Using Phylogenies. (27th August 2019) - Kosakovsky Pond, Sergei L; Poon, Art F Y; Velazquez, Ryan; Weaver, Steven; Hepler, N Lance; Murrell, Ben; Shank, Stephen D; Magalis, Brittany Rife; Bouvier, Dave; Nekrutenko, Anton; Wisotsky, Sadie; Spielman, Stephanie J; et al.
Abstract: HYpothesis testing using PHYlogenies (HyPhy) is a scriptable, open-source package for fitting a broad range of evolutionary models to multiple sequence alignments, and for conducting subsequent parameter estimation and hypothesis testing, primarily in the maximum likelihood statistical framework. It has become a popular choice for characterizing various aspects of the evolutionary process: natural selection, evolutionary rates, recombination, and coevolution. The 2.5 release (available from www.hyphy.org ) includes a completely re-engineered computational core and analysis library that introduces new classes of evolutionary models and statistical tests, delivers substantial performance and stability enhancements, improves usability, streamlines end-to-end analysis workflows, makes it easier to develop custom analyses, and is mostly backward compatible with previous HyPhy releases.